Quantum Cascade Laser Infrared Spectroscopy for Online Monitoring of Hydroxylamine Nitrate - Marissa E. Morales-Rodriguez; Joanna McFarlane; Michelle K. Kidder (International Journal of Analytical Chemistry)
We describe a new approach for high sensitivity and real-time online measurements to monitor the kinetics in the processing of nuclear materials and other chemical reactions. Mid infrared (Mid-IR) quantum cascade laser (QCL) high-resolution spectroscopy was used for rapid and continuous sampling of nitrates in aqueous and organic reactive systems, using pattern recognition analysis and high sensitivity to detect and identify chemical species. In this standoff or off-set method, the collection of a sample for analysis is not required. To perform the analysis, a flow cell was used for in situ sampling of a liquid slipstream. A prototype was designed based on attenuated total reflection (ATR) coupled with the QCL beam to detect and identify chemical changes and be deployed in hostile environments, either radiological or chemical. The limit of detection (LOD) and the limit of quantification (LOQ) at 3σ for hydroxylamine nitrate ranged from 0.3 to 3 and from 3.5 to 10 g·L−1, respectively, for the nitrate system at three peaks with wavelengths between 3.8 and 9.8 μm.